2022
DOI: 10.1002/chem.202201731
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Ultrafast Charge Transfer Population: Insights from the Quantum Dynamics of Guanine‐Cytosine in Chloroform

Abstract: We study the ultrafast photoactivated dynamics of the hydrogen bonded dimer Guanine‐Cytosine in chloroform solution, focusing on the population of the Guanine→Cytosine charge transfer state (GC‐CT), an important elementary process for the photophysics and photochemistry of nucleic acids. We integrate a quantum dynamics propagation scheme, based on a linear vibronic model parameterized through time dependent density functional theory calculations, with four different solvation models, either implicit or explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Furthermore, for an example snapshot at 2000 ns that shows significant oscillations, we compute and plot the off diagonal elements of the density matrix ρ LE , CT ( t ) = Tr { | CT LE | ρ̂ false( t false) } for a more direct measure of the coherence, as shown in Figure S19. We noticed similar behavior for the population of a CT state in a GC Watson–Crick pair in ref . These coherences are essentially washed-out when the populations are averaged over a number of simulations.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, for an example snapshot at 2000 ns that shows significant oscillations, we compute and plot the off diagonal elements of the density matrix ρ LE , CT ( t ) = Tr { | CT LE | ρ̂ false( t false) } for a more direct measure of the coherence, as shown in Figure S19. We noticed similar behavior for the population of a CT state in a GC Watson–Crick pair in ref . These coherences are essentially washed-out when the populations are averaged over a number of simulations.…”
Section: Resultssupporting
confidence: 75%
“…The latter path, in fact, additionally extends the capability of the Ad-MD|gLVC protocol, introducing the possibility to treat multichromophore systems, with possible intra-site internal conversions, while taking into account inter-state coupling and inter-molecular structural distortion effects. A similar extension was already employed to study the formation of CT states in guanine–cytosine in explicit solvent models …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…A similar extension was already employed to study the formation of CT states in guanine−cytosine in explicit solvent models. 49 2.…”
Section: General Scheme Of the Computational Protocolmentioning
confidence: 99%
“…Recently, Green et al calculated the dynamics of G-C for different excited states and found a rapid population transfer at S 4 . 36 It is worth noting that the absorption peak in Fig. 1(b) comes from the fourth excited state (S 4 ), which corresponds to the strongest oscillator strength ( f = 0.0959) in Table S3 (ESI †).…”
Section: Photoinduced Charge Transfermentioning
confidence: 99%